(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
This research investigated the development innovative of a waste plastic-sand mixer for sustainable paver block production. The Full Factorial Design (FFD) at two factors, two levels with four experimental runs were chosen to obtain the paver blocks with high compressive strength. The low (-1) and high (+1) levels for the plastic waste were set to be 30% weight and 40% weight while that for the sand, were 40% weight and 70% weight. ANOVA was employed for the analysis to know the most significant factor for compressive strength. It was observed that plastic waste was the most significant factor responsible for good compressive strength as shown by the F-statistics. The plastic-sand paver blocks produced were subjected to compression tests in accordance with ASTM C140 specification, SEM - (Scanning Electron Microscopy) and Vickers micro-hardness test. From the FFD, it was observed that the crushing force exerted on the paver blocks increased with an increase in the weight and density of the paver. The maximum compressive strength was seen to be 0.75 N/mm2 for a paver block weight of 0.936 kg. The SEM morphology results showed a bond of a white farinaceous layer which indicates the presence of silica obtained from the sand and the black colour which indicates the plastic waste used. The waste plastic/sand mixer was successfully achieved at a cost of 185 which is far cheaper compared to the foreign-made, whose prices range from 1,200 to 12,000, and the prevailing market cost of concrete paver block ranges from 0.73 – 2.18. The study concludes that plastic-sand paver blocks are candidate materials that could be used as substitutes for concrete pavers